Infliximab-induced liver injury: Clinical phenotypes, autoimmunity and the role of corticosteroid treatment. - Björnsson, Helgi Kristinn; Gudbjornsson, Bjorn; Björnsson, Einar Stefan (Journal of Hepatology, 2022)
To access publisher's full text version of this article click on the hyperlink below Background & aims: Infliximab has been associated with drug-induced liver injury (DILI), particularly drug-induced autoimmune hepatitis (DIAIH). DIAIH is commonly treated with corticosteroids, but there is limited data on the efficacy of corticosteroids in infliximab-induced DILI. Methods: Patients were included for assessment if they had been treated with infliximab between 2009-2020 in Iceland and had developed elevated liver tests. Other specific etiologies of liver enzyme elevations were excluded. Patients treated with corticosteroids were compared to patients not receiving corticosteroids. Results: A total of 36 patients with infliximab-induced DILI were identified: median age was 46 years (IQR 32-54) and 28 (78%) were female. Type of liver injury was predominantly hepatocellular (64%). Median peak liver enzymes were: alanine aminotransferase (ALT) 393 (328-695) U/L, aspartate aminotransferase 283 (158-564) U/L, alkaline phosphatase 116 (83-205) U/L, and bilirubin (10-20) 13 μmol/L. A total of 25 (69%) were positive for anti-nuclear antibody and/or had elevated IgG. Corticosteroids were initiated in 17 (47%). Median time from onset of liver injury to peak ALT value was longer in patients treated with corticosteroids, 22 (12-59) vs. 0 (0-3) days (p = 0.001). Time from peak ALT to normalization of liver enzymes was 45 days in the corticosteroid group vs. 77 days in others (p = 0.062). Corticosteroids were tapered in all patients, with no cases of relapse during the follow-up period of 1,245 (820-2,698) days. Overall 75% received another biologic, mostly adalimumab, without evidence of liver injury. Conclusion: Approximately half of patients with infliximab-induced liver injury had slow improvement in ALT despite cessation of therapy and were treated with corticosteroids. Treatment response was good with prompt resolution of liver test abnormalities. Relapse of liver injury was not observed after tapering of ...